Risks and long-term benefits of hormone replacement therapy by - Hillard, T. (2015)
There is a consensus that the long-term consequences of ovarian deprivation can be prevented or reduced by trabecular bone therapy in one out of two cases resulting in lifetime risks of osteoporotic fractures. Hormone replacement therapy (HRT) prevented this loss of bone and decreases the incidence of fractures. a minimum of 5 years of treatment is recommended to achieve significant benefits. Epidemiologic evidence is accumulating in that postmenopausal estrogen therapy reduces the risk of cardiovascular disease and stroke by about 30% and 70%, even in the presence of established risk factors. Given the frequency of cardiovascular disease, it becomes probably one of the original advantages of using hormone replacement therapy in the next decade. Concerns about the long-term safety of HRT have focused on breast and endometrial cancer. The increased risk of endometrial cancer associated with estrogen-only therapy is decreased with the sequence of adding progesterone for 10 to 12 days of each cycle. The possible effect of therapy (HRT) regarding breast cancer risk should be considered against experiences that indicate that one in 12 develop the disease. Epidemiological studies investigating this relationship are reviewed in this paper. There is a large consensus that using hormone replacement therapy (HRT) with a duration of 5 to 6 years does not increase the risks of breast cancer. Therapies longer (10-15 years) have been reported, which increase this risk, although not all the information is consistent. Other factors such as family history and benign breast diseases, could also influence the risk of cancer. The potential benefits of hormone replacement therapy against mortality and morbidity are enormous. Against this there is a possible small increased risk of breast cancer with long-term treatment. You should look for better understanding of the long-term consequences of menopause and potential benefits of TSH, so that women can make informed decisions about the need for hormone replacement therapy by.